2013
DOI: 10.1155/2013/351756
|View full text |Cite
|
Sign up to set email alerts
|

The Range of Prey Size of the Royal Bengal Tiger of Sundarbans

Abstract: Relatively little is known about the feeding habit of the Royal Bengal Tiger of Sundarbans and the relative biomass of individual prey base species that the predator consumes during each kill. This is the first attempt to collect such data from the study area. Data sets of two phases have been used. Identification of undigested remains of 214 tiger scat samples was carried out. A comparison with Sundarbans tigers in zoo has been made. In its natural habitat, the tiger consumes more of spotted deer, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A study on Iberian lynx has also reported the higher abundance of these enzymes in the gut microbiota (Alcaide et al, 2012). Although the diet of these Panthera species mostly comprises of higher vertebrates, a few studies have reported the presence of plant biomass in the scats of leopards, lions, and tigers (Hoppe-Dominik, 1988;Cashman et al, 1992;Mukherjee and Sen Sarkar, 2013;Stein and Hayssen, 2013). Thus, these findings suggest that the gut microbiome of wild felids not only harbors gene sets for the uptake of sugars from primary animal tissues but also from the plant biomass.…”
Section: Discussionmentioning
confidence: 93%
“…A study on Iberian lynx has also reported the higher abundance of these enzymes in the gut microbiota (Alcaide et al, 2012). Although the diet of these Panthera species mostly comprises of higher vertebrates, a few studies have reported the presence of plant biomass in the scats of leopards, lions, and tigers (Hoppe-Dominik, 1988;Cashman et al, 1992;Mukherjee and Sen Sarkar, 2013;Stein and Hayssen, 2013). Thus, these findings suggest that the gut microbiome of wild felids not only harbors gene sets for the uptake of sugars from primary animal tissues but also from the plant biomass.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, the STR was recently accredited by the “CATS Honour” by National Tiger Conservation Authority for its excellent tiger conservation. [ 41 ] This is a piece of good news, and we welcome it. Still, equally, we are eager to see a giant step from all the stakeholders to mitigate climate change impact and livelihood provision for the entire population of Sundarban.…”
Section: Discussionmentioning
confidence: 94%
“…As in other cases, this phenomenon is not restricted to South America. In the Sundarbans mangrove of India, tigers prey on water monitors (Varanus salvadorii) that represent as much as 12% of their diet (Mukherjee and Sarkar, 2013). In Africa, fish eagles (Haliaeetus vocifer) and crowned eagles (Stephanoaetus coronatus) are known to prey on the semiaquatic Nile monitor (Boshoff and Palmer, 1994;Stewart et al, 1997), which in turn is a predator of crocodile nests and juveniles (Kofron, 1989).…”
Section: Reptiles As Nutrient Transportersmentioning
confidence: 99%